The Anion-Binding Approach to Catalytic Enantioselective Acyl Transfer - Seidel, Daniel (Synlett, 2014)
This account details the development of a dual-catalysis approach and its application to the kinetic resolution of amines and other enantioselective acyl-transfer reactions. Anion recognition is an essential design element of these processes, which are enabled by the combined action of an achiral 4-(N,N-dimethylamino)pyridine (DMAP) derivative and a chiral anion receptor catalyst.1 Introduction2 Kinetic Resolution of Amines2.1 Benzylic Amines2.2 Propargylic Amines2.3 Allylic Amines2.4 Benzylic Amines Revisited2.5 Racemic Diamines3 Desymmetrization of meso-Diamines4 Miscellaneous Acyl Transfer Reactions4.1 Steglich Reaction4.2 Reactions of Isoquinolines with Azlactones4.3 Acylation of Silyl Ketene Acetals5 Conclusions
Keywords: asymmetric catalysis; amines; acylation; kinetic resolution; desymmetrization